Functions of Sentences in Instagram Captions - Rifa Yehan Fezqina; Siti Yuliah; Khoirun Nisaa' Arnoi (Jurnal Bahasa Inggris Terapan, 2025)
This study investigated the functions of sentences used in Colorbox's Instagram captions applying Greenbaum & Nelson (2009) framework: declarative, interrogative, imperative, and exclamatory. The aims of this study were to identify and analyze their use and to identify which types are the most frequently utilized. To achieve these objectives, 30 captions containing 58 sentences posted by Colorbox from January to December 2024 were selected using purposive random sampling. The captions were analyzed using qualitative methods. Each sentence in the text was examined and categorized based on its function. The results showed that imperative sentences are the most frequently used (46%), followed by interrogative sentences (28%), declarative sentences (21%), and exclamation sentences (5%). Imperative sentences are often used to encourage actions such as commenting or tapping on a link. The other sentence types are used to provide information, ask questions, or express emotions. These findings showed that Colorbox uses sentence functions effectively to communicate and interact with its audience. The results of this study give two implications both theoretically and practically. Theoretically, the results enrich the knowledge on functions of sentences. Practically, the results provide an insight for content creators and marketing practitioners to write more interesting, clear, and engaging captions.